The Role of Islamic Commercial Banks in the Recovery of the National Economy Affected by the Pandemic in Indonesia - Tia Angraini Safitri; Asnaini Asnaini; Idwal Idwal (Penerbit Jurnal Indonesia, 2021)
This research was conducted to test and analyze the role of Islamic Commercial Banks in encouraging the rate of economic growth affected by the pandemic in Indonesia for 2 (two) years from 2019 to 2020. The purpose of this study is to see how much influence commercial banks have. sharia. on the National Economic Recovery affected by the pandemic in Indonesia. Growth from 2019 to 2020. The number of data sets is 8 (eight) quarters of the data on the development of Gross Domestic Product (GDP), third party funds of Islamic commercial banks, financing provided by Islamic commercial banks, and Liquidity funds of Islamic commercial banks. Islamic commercial bank. This study uses a quantitative approach. The analytical model used in this study is a time series data regression analysis model. The output results show that the independent variable X1 is -0.546161, X2 is 0.668608 meaning it has a value above 0.05, then X1 and X2 partially have no effect on Y or H1 is rejected. While X3 of 0.043179 means that it has a value below 0.05 then partially affects Y or H1 is accepted.